(untitled) (Journal of Educational Sciences, 2020)
Today in the world there are more than seven thousand different languages. In international circles, business, science and other fields of activity, English prevails as the main language of communication. In the era of globalization of the world, Kazakhstan is actively implementing a program to modernize the education system, the aim of which is to switch to a trilingual education system in secondary schools. Currently, CLIL learning technology is gaining popularity around the world as a new curriculum for learning an additional language. According to the studies, the use of CLIL technology in the classroom improves the educational environment of the class, shortens the learning time and, moreover, makes the teaching concept wider and deeper. Despite all its advantages, CLIL can be difficult in some respects. In view of the complexity of this topic, it is important to have an idea of how effectively the implementation of CLIL training technology in Kazakhstan is taking place. This article presents the results of a survey of 127 teachers about the experience of implementing CLIL technology in secondary schools in Kazakhstan. The survey was conducted on social networks for teachers through Whatsapp and Telegram applications based on the Google Forms platform. Key words: CLIL technology, education, trilingualism, modernization.